Augmentation of Financial Inclusion : A Structured Review from the Indian Perspective - Choudhury, Rituparna; Gupta, Sumeet (Indian Journal of Finance, 2025)
Purpose : This research study placed more stress on the underbanked rather than the unbanked, as the accessibility and availability are almost achieved, but the goal of utilization and standard quality of financial services still needed to be accomplished, which accounts for a huge percentage of financial inclusion. There are still areas where improvements need to be made. Methodology : We divided the review articles into pertinent themes using a systematized thematic literature review methodology. Findings : We found that after India’s demonetization in 2016, a substantial body of research on the subject surfaced. India achieved its cashless society goal with the Unified Payment Interface’s implementation, which further enhanced digital financial inclusion. Despite efforts to promote a cashless society, physical currency circulation continued to rise as people preferred to keep cash for emergencies post-COVID-19. The review report ended with a few recommendations for further investigation. Practical Implications : It is recommended to increase the percentage of quality parameters in the financial inclusion index in order to have proper management of financial inclusion. The government must focus on retaining account holders and improving service quality. Although our research has limitations, it provides room for future additional research. Originality/Value : A thematic evaluation of the literature on financial inclusion in India is provided in this study, outlining the primary methodology and authors’ perspectives and highlighting key areas for further research.